2019
DOI: 10.3390/ijms20235902
|View full text |Cite
|
Sign up to set email alerts
|

The Knockdown of TREK-1 in Hippocampal Neurons Attenuate Lipopolysaccharide-Induced Depressive-Like Behavior in Mice

Abstract: TWIK-related potassium channel-1 (TREK-1) is broadly expressed in the brain and involved in diverse brain diseases, such as seizures, ischemia, and depression. However, the cell type-specific roles of TREK-1 in the brain are largely unknown. Here, we generated a Cre-dependent TREK-1 knockdown (Cd-TREK-1 KD) transgenic mouse containing a gene cassette for Cre-dependent TREK-1 short hairpin ribonucleic acid to regulate the cell type-specific TREK-1 expression. We confirmed the knockdown of TREK-1 by injecting ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Clearly, antidepressant effects have been reported in both TREK-1 KO mice and mice treated with spadin, a specific TREK-1 inhibitor [ 23 , 53 ]. Recently, we also reported specific KD of TREK-1 in the hippocampal neurons revealed antidepressant effects [ 54 ], suggesting that inhibition of TREK-1 in neurons is important for antidepressant phenotypes. However, in the present study, we clearly demonstrated that astrocytic TREK-1 is critical for passive conductance, and spadin, a potent antidepressant drug, can efficiently inhibit astrocytic passive conductance.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, antidepressant effects have been reported in both TREK-1 KO mice and mice treated with spadin, a specific TREK-1 inhibitor [ 23 , 53 ]. Recently, we also reported specific KD of TREK-1 in the hippocampal neurons revealed antidepressant effects [ 54 ], suggesting that inhibition of TREK-1 in neurons is important for antidepressant phenotypes. However, in the present study, we clearly demonstrated that astrocytic TREK-1 is critical for passive conductance, and spadin, a potent antidepressant drug, can efficiently inhibit astrocytic passive conductance.…”
Section: Discussionmentioning
confidence: 99%
“…Both spadin and SID1900 enhanced the excitability of serotonergic neurons in mice, alleviating depressive symptoms [57,58]. TREK-1 knockdown in hippocampal neurons alleviated depressive symptoms in a mouse model of lipopolysaccharideinduced depression [61]. Consistent with the studies on rodent models, four single nucleotide polymorphisms in TREK-1 were also identified in some patients with treatment resistance in major depressive disorders [62] These observations suggest that TREK-1 may be a useful therapeutic target in depression.…”
Section: Treksmentioning
confidence: 60%
“…While TREK/TRAAK mechanosensitivity is clearly important in some tissues (see below), elsewhere, the mechanical stimulation appears to be less probable and the channels are mainly controlled by other regulatory factors. The members of the TREK subfamily are abundantly expressed at several locations (e.g., widespread expression in the neurons of the different brain regions [50][51][52][53][54], or high TREK-1 expression in the human adrenal gland [55,56]), where it is far from certain whether, or how, the cellular responsiveness to mechanical stimuli contributes to the physiological function.…”
Section: Introductionmentioning
confidence: 99%